Inter-functional Knowledge Sharing about Stakeholder Requirements in International Investment Projects - Heikkilä, Tero (My University, 2011)
The research approaches inter-functional knowledge sharing in international investment projects focusing on knowledge about stakeholder requirements. The aim is to answer what factors impede knowledge sharing in these circumstances. In the theoretical review generic knowledge sharing inhibitors are discussed under the AMO framework together with potential problems with knowledge sharing in the particular circumstances of the research. All of the inhibitors are compiled in an integrative framework which is used to guide the empirical part of the research. The research is a qualitative case study using a company division engaged in investment projects in various countries as the case example. Data about the research subject was collected by conducting five theme interviews with representatives of sales and four with representatives of delivery department of the case organization. The issues the interviewees highlighted were analyzed within the departments after which the departments collectively were contrasted with each other. Problems were assumed to exist where the interviewees agreed on while further study is needed when it comes to issues of which consensus was not reached. The findings showed that although the interviewees from the sales department disagreed with their colleagues from the delivery department regarding the overarching problem, consensus about several specific knowledge sharing inhibitors existed. These inhibitors highlighted the fact that difficulties with knowledge sharing between the case organization’s sales and delivery department are faced due to an apparent disconnection between the departments. Consequently, opportunity to share knowledge is reduced as individuals do not interact and generally lack contact. Motivation to share knowledge also suffers as the departments turn inwards focusing on their own tasks and goals. Finally, ability to share knowledge is reduced as well since the departments lack understanding towards each other’s environments and subsequent needs for knowledge.
Keywords: Knowledge sharing; inter-functional; international investment projects; stakeholder requirements; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|